THE EFFECT OF MONETARY FACTORS ON THE EXCHANGE RATE: A STUDY WITH VECM APPROACH - Nugrahani, Eva Idvi; Dwi Atmanti, Hastarini (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of monetary factors on the exchange rate of the Rupiah against the US Dollar using the Vector Error Correction Model (VECM) approach. The variables used include interest rates, inflation, and foreign exchange reserves as independent variables, and exchange rates. The data used is annual data from 1988 to 2023 obtained from official sources such as Bank Indonesia, BPS, and World Bank. The stationarity test results show that all variables are (1). The cointegration test shows that there is a long-term relationship between variables. Model estimation shows that interest rates and inflation have a significant effect on the exchange rate in the short term, while foreign exchange reserves play a role in the long term. The impulse response and variance decomposition results corroborate that exchange rate fluctuations are mostly influenced by shocks to interest rates and inflation. This study emphasizes the importance of monetary management in maintaining exchange rate stability.